(untitled) (Revista Contexto & Educação, 2025)
The article aims to present the results of a research that collects data on the judicial review involving the occupation of racial quota, considering the affirmative action policies in Brazilian universities. This is a survey carried out in the Federal University of Ceará, covering the period from 2019 to 2023, in which 78 lawsuits and their preliminary, final and appeal decisions were consulted. The presentation and analysis of the data was preceded by a presentation of the foundations and objectives of affirmative action policies and the use of terms such as identity, hetero-identification and intersectionality. This is exploratory research, with literature review and data collection and analysis.